Resistance strategies and sexual assault outcomes: do measurement decisions influence empirical findings? - O'Neal, Eryn Nicole (Criminology, criminal justice, law & society, 2015)
Research examining resistance strategies and sexual assault outcomes has resulted in inconsistent findings. In order to substantially contribute to this body of literature, we estimate the effects of several resistance strategy measures on victim injury outcomes andrape completion. We attempt to determine whether resistance measurement decisions influence empirical results. Findings suggest that measurement matters. Results indicate that the effects of resistance strategies on injurious outcomes and rape avoidance vary depending on operationalization and measurement techniques. This knowledge informs a methodological direction for future sexual assault resistance research. Practical implications and suggestions for future research are discussed